Peran Mammografi Untuk Skrining Kanker Payudara: Sebuah Tinjauan Pustaka - Soekersi, Hari; Azhar, Yohana; Akbari, Kiran Shadentyra (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Breast cancer is the most common cancer among women in Indonesia. The cure rate can be increased by early detection and appropriate therapy. The early detection modality recommended by WHO is screening mammography. The aim of this study was to determine the role and advantages and disadvantages of mammography compared to other modalities through narrative literature review with 30 literature that met the inclusion and exclusion criteria. The advantages of screening mammography are reducing mortality, increasing early treatment, and improving the quality of diagnostics as a follow-up to the results of screening. The disadvantages of this modality are overdiagnosis, false alarm, interval cancer, and radiation risk. Screening mammography can be combined with other modalities to increase accuracy such as MRI in high-risk women and ultrasound in women with denser breasts. The recommendation to initiate routine screening mammography at one year is 40 years. Barriers that often occur in lower middle-income countries are lack of knowledge and awareness, unavailable infrastructure and resources, accessibility, inadequate costs and the persistence of fear and shame. Therefore, the benefits of screening outweigh the risks and can be combined with other modalities to increase accuracy.